Evaluation of ligand modified poly (N-Isopropyl acrylamide) hydrogel for etiological diagnosis of corneal infection. (January 2022) - Shivshetty, Nagaveni; Swift, Thomas; Pinnock, Abigail; Pownall, David; Neil, Sheila Mac; Douglas, Ian; Garg, Prashant; Rimmer, Stephen
Abstract: Corneal ulcers, a leading cause of blindness in the developing world are treated inappropriately without prior microbiology assessment because of issues related to availability or cost of accessing these services. In this work we aimed to develop a device for identifying the presence of Gram-positive or Gram-negative bacteria or fungi that can be used by someone without the need for a microbiology laboratory. Working with branched poly (N- iso propyl acrylamide) (PNIPAM) tagged with Vancomycin, Polymyxin B, or Amphotericin B to bind Gram-positive bacteria, Gram-negative bacteria and fungi respectively, grafted onto a single hydrogel we demonstrated specific binding of the organisms. The limit of detection of the microbes by these polymers was between 10 and 4 organisms per high power field (100X) for bacteria and fungi binding polymers respectively. Using ex vivo and animal cornea infection models infected with bacteria, fungi or both we than demonstrated that the triple functionalised hydrogel could pick up all 3 organisms after being in place for 30 min. To confirm the presence of bacteria and fungi we used conventional microbiology techniques and fluorescently labelled ligands or dyes. While we need to develop an easy-to-use either a colorimetric or an imaging system to detect the fluorescent signals, this study presents for the first time a simple to use hydrogel system, which can be applied to infected eyes and specifically binds different classes of infecting agents within a short space of time. Ultimately this diagnostic system will not require trained microbiologists for its use and will be used at the point-of-care. Highlights: Functionalised branched Poly N-isopropyl acrylamide binds corneal ulcer causing microorganisms. The functionalised polymers demonstrated specific binding to gram positive, gram negative and fungi. Grafting three different polymers on a single hydrogel retained this specific binding for microorganisms. Triple functionalised hydrogels were effective in picking up microorganisms in ex-vivo and animal cornea infection models. Application for a duration of 30 min was sufficient to pick up enough organisms for subsequent identification.